A Virtual Reality Teaching Simulation for Exercise During Pregnancy - Setiawan, Abas; Agiwahyuanto, Faik; Arsiwi, Pramudi (International Journal of Emerging Technologies in Learning (iJET), 2019)
One of the poor indicators of the development and health status of a country is high maternal mortality. The world has seen that one pregnant woman in every two minutes dies because of complication with serious or long-lasting consequences. During pregnancy, pregnant women tend to reduce physical activity due to increased sensitivity factors. It will lead to decrease the elasticity of muscles and joints. The way to improve the elasticity is doing exercise during pregnancy. But, there are still many pregnant women who are less interested in doing exercise during pregnancy, due to high loaded in working day and dense schedule of daily activities in her career or as a housewife. Some women assume that by attending pregnancy exercise course in hospitals or health care centers is time-consuming and too formal because they have to follow the prenatal personal trainer schedule. The technology that allows helping pregnant women in exercise during pregnancy is virtual reality. In this study, the development of virtual reality application for exercise during pregnancy adapted from the methodology to determine when to use virtual reality in education and training combined with the Immersive Virtual Environment (IVE) questionnaire. The average results of overall components in the IVE questionnaire is 4.26 of 5-point scales that indicates the virtual reality application for exercise during pregnancy is feasible to use by pregnant woman.